Review of the impact of urban parks on public health during the Covid-19 Pandemic / Xuanxian Chen and Massoomeh Hedayati Marzbali - Chen, Xuanxian; Marzbali, Massoomeh Hedayati (Universiti Teknologi MARA, Perak, 2023)
The COVID-19 pandemic may have changed the effects that urban parks have on their users. The purpose of this study was to understand the mental health effects of the pandemic, explore the role of urban parks on human health, and propose future research directions. We conducted a literature review on the impact of the COVID-19 pandemic on the effects of urban parks on human health and well-being. Using five screening criteria, we selected 32 articles published in the Scopus, Mendeley, and Google Scholar databases for analysis. We chose a systematic literature review as the methodology because it allowed the identification of literature relevant to the research questions. We conducted a systematic study based on the characteristics of the selected articles and the operationalization of variables, reported the results, and made recommendations. The results indicated that people went to parks to relieve stress caused by the pandemic, although some were deterred because they perceived risk in visiting public parks and green spaces. Others focused more on the Internet while in green spaces than on taking advantage of park activities Demands for safety, accessibility for all, and interesting environments will force urban parks to change. There were insufficient practical studies offering novel design ideas and examining the health impacts of small, regional urban parks during the pandemic.